Value of biomarkers in predicting mortality in older medical emergency department patients: a Dutch prospective study. Issue 1 (31st January 2021) - Zelis, Noortje; Hundscheid, Robin; Buijs, Jacqueline; De Leeuw, Peter W; Raijmakers, Maarten TM; van Kuijk, Sander MJ; Stassen, Patricia M
Abstract : Objective: Older emergency department (ED) patients are at high risk of mortality, and it is important to predict which patients are at highest risk. Biomarkers such as lactate, high-sensitivity cardiac troponin T (hs-cTnT), N-terminal pro-B-type natriuretic peptide (NT-proBNP), D-dimer and procalcitonin may be able to identify those at risk. We aimed to assess the discriminatory value of these biomarkers for 30-day mortality and other adverse outcomes. Design: Prospective cohort study. On arrival of patients, five biomarkers were measured. Area under the curves (AUCs) and interval likelihood ratios (LRs) were calculated to investigate the discriminatory value of the biomarkers. Setting: ED in the Netherlands. Participants: Older (≥65 years) medical ED patients, referred for internal medicine or gastroenterology. Primary and secondary outcome measures: 30-day mortality was the primary outcome measure, while other adverse outcomes (intensive care unit/medium care unit admission, prolonged length of hospital stay, loss of independent living and unplanned readmission) were the composite secondary outcome measure. Results: The median age of the 450 included patients was 79 years (IQR 73–85). In total, 51 (11.3%) patients died within 30 days. The AUCs of all biomarkers for prediction of mortality were sufficient to good, with the highest AUC of 0.73 for hs-cTnT and NT-proBNP. Only for the highest lactate values, the LR was high enough (29.0) to be applicable for clinical decision making, but this applied to a minority of patients. The AUC for the composite secondary outcome (intensive and medium care admission, length of hospital stay >7 days, loss of independent living and unplanned readmission within 30 days) was lower, ranging between 0.58 and 0.67. Conclusions: Although all five biomarkers predict 30-day mortality in older medical ED patients, their individual discriminatory value was not high enough to contribute to clinical decision making. Trial registration number: NCT02946398; Results .